Course syllabi in GIS programming: Trends and patterns in the integration of computer science and programming. - Bowlick, Forrest J.; Bednarz, Sarah W.; Goldberg, Daniel W. (Canadian Geographer)
Understanding of fundamentals of computer science and abilities in programming are becoming more important components of the GIS practitioner's skillset. As the frontiers of GIS expand into areas of inquiry and modes of operation which require such domain capabilities, teaching and instruction in GIS must begin that shift as well. And while the knowledge, skills, and practices of the GIS practitioner have always been in flux, the range of potential topics from computer science and programming to integrate into GIS instruction is a major pedagogical challenge. This paper examines a range of syllabi from variant GIS programming courses to explore the landscape of programming coursework. Through content analysis, these syllabi reveal three general themes: courses built on learning scripting with Python, courses built on learning fundamentals of WebGIS, and courses built on learning fundamentals in geodatabase design and management. While each of these focus areas are impactful skills for GIS learners to explore, there is by no means any consistency or cohesion in how GIS programming courses operate, nor does there seem to be any general resources or approaches to unify course design. More work is necessary among GIS instructors to begin building evidence‐based practices in GIS programming instruction.